The PMDB’s ideological behaviour at the Chamber of Deputies in 2013 - Linhares, Bianca de Freitas (2020)
The article aims at analysing the ideological behaviour of PMDB’s federal deputies in 2013. We depart from the idea that to set a political party specifically in a particular ideological point does not allow to grasp its heterogeneity. To achieve this goal, we present a different methodology. Law projects have been classified based on a chart of meanings built from federal deputies’ speeches of all parties. In a general way, results confirm a trend already outlined by the literature, that is, the PMDB occupies a position at the centre. However, in this text, we demonstrate essential variations on the left and right in this spectrum. In this sense, although the party can be classified at a specific point in the ideological spectrum, the main article’s finding is that this point cannot be perceived in an essentialist way. Such a point shows significant variations that need to be considered.